2006
DOI: 10.1111/j.1365-2958.2006.05223.x
|View full text |Cite
|
Sign up to set email alerts
|

The mode of action of the lantibiotic lacticin 3147 – a complex mechanism involving specific interaction of two peptides and the cell wall precursor lipid II

Abstract: Lacticin 3147 is a two-peptide lantibiotic produced by Lactococcus lactis in which both peptides, LtnA1 and LtnA2, interact synergistically to produce antibiotic activities in the nanomolar concentration range; the individual peptides possess marginal (LtnA1) or no activity (LtnA2). We analysed the molecular basis for the synergism and found the cell wall precursor lipid II to play a crucial role as a target molecule. Tryptophan fluorescence measurements identified LtnA1, which is structurally similar to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
191
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(201 citation statements)
references
References 40 publications
5
191
0
Order By: Relevance
“…The latter mechanism is known from some two-peptide lantibiotics, such as lacticin 3147, where significant antibiotic activity is only achieved through the cooperative action of two peptides. Peptide A contains a mersacidin-like lipid II binding motif and binds to the CW precursor; the second peptide is then able to dock to the peptide⅐lipid II complex, allowing the complex to insert into the membrane to form a defined pore (56). We did not find evidence for a dimerization in solution, but the data showed clear evidence for two separate events in NAI-107⅐lipid II binding, a relatively strong initial interaction leading to the disappearance of free lipid II resonances and a weaker subsequent interaction leading to the appearance of bound lipid II and NAI-107 resonances (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The latter mechanism is known from some two-peptide lantibiotics, such as lacticin 3147, where significant antibiotic activity is only achieved through the cooperative action of two peptides. Peptide A contains a mersacidin-like lipid II binding motif and binds to the CW precursor; the second peptide is then able to dock to the peptide⅐lipid II complex, allowing the complex to insert into the membrane to form a defined pore (56). We did not find evidence for a dimerization in solution, but the data showed clear evidence for two separate events in NAI-107⅐lipid II binding, a relatively strong initial interaction leading to the disappearance of free lipid II resonances and a weaker subsequent interaction leading to the appearance of bound lipid II and NAI-107 resonances (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The biological activity displayed by these mature products depended on the presence of both modified peptides in the bioassay. Ltn␣ of lacticin 3147 and BHT␣ exhibit low level antibacterial activity by themselves, presumably by weak binding to lipid II (12,30). It is possible that Hal␣ may also demonstrate biological activity at higher concentrations, but so far we have been limited in the accessible concentrations of in vitro product because of its poor solubility.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the mode of action of lacticin 3147 demonstrated that Ltn␣ binds to the peptidoglycan precursor lipid II (12), a result that was anticipated because of the structural similarity between Ltn␣ and mersacidin, which also binds to lipid II (13). However, in order for lacticin 3147 to inhibit cell wall biosynthesis and form small pores in the cell membrane, Ltn␤ is also necessary, leading to a proposed model in which the lipid II:Ltn␣ complex recruits Ltn␤ to form an active complex (12,14).…”
mentioning
confidence: 99%
“…6 Two-component lantibiotics may exert only one of these modes of action (binding to lipid II) when administered independently and both modes of action when used together (lipid II binding and pore formation). 9 There are still fundamental challenges to the successful utilization of many lantibiotics as therapeutic agents. Thus far, their use has been limited to topical applications, as many of these peptides are prone to degradation by enzymes present in the gastrointestinal tract.…”
Section: Lantibioticsmentioning
confidence: 99%